EXPERIMENTAL STUDIES OF GRAIN DRYING WITH MW – CONVECTIVE CYCLIC ENERGY SUPPLY - Бошкова, Ірина; Волгушева, Наталя; Бошков, Леонід; Капауз, Катерина (SWorldJournal, 2024)
The paper presents the results of a study of drying a dense layer of grain under conditions of using microwave field energy. Cyclic modes of supplying microwave energy to a layer of material, alternating with periods of air blowing, are considered. The in